2022
DOI: 10.37335/ijek.v10i1.159
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Quantitative Methods in Business Practice: Study of Czech Republic

Abstract: The purpose of the study is to evaluate the use of quantitative methods in companies and determine the reasons for the non-use of quantitative methods. First, the context of dependence on individual characteristics of the company, such as size, amount of foreign share, and business sector, is analysed. Subsequently, the methods companies use, and those for which companies require scientific support and research are identified. The study is carried out in companies in the Czech Republic and is based on an elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…The main limitations of this study are, of course, the application to the data of one type of business. As already mentioned in the discussion chapter, research in this area should be continued, as evidenced by another study by the authors (Kolková et al, 2022). Using forecasting methods during periods of demand stability and low volatility is easy.…”
Section: Discussionmentioning
confidence: 87%
“…The main limitations of this study are, of course, the application to the data of one type of business. As already mentioned in the discussion chapter, research in this area should be continued, as evidenced by another study by the authors (Kolková et al, 2022). Using forecasting methods during periods of demand stability and low volatility is easy.…”
Section: Discussionmentioning
confidence: 87%
“…The use of more complex ML models in practice is still limited to large enterprises. Kolková et al (2022), in their research, focused on SMEs, and large enterprises, confirmed that SMEs do not widely use quantitative methods for their decision-making. The main reason for not using quantitative methods in SMEs was that they are too academically demanding and that their use in practice is often unrealistic due to their complexity.…”
Section: Literature Reviewmentioning
confidence: 88%
“…However, most companies still focus on forecasting, although not at the top of it. Forecasting future business development is considered the most for future research (Kolková et al, 2022). At the same time, the research should lead to simplification and more direct applicability and interpretability of methods.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of innovative technologies has a significant impact on business indicators (Civelek et al, 2021a), forecasts, order rates, logistics and automation, as well as the ability to control and advertise. Such innovations are important due to the transformation (Civelek et al, 2021b), profitability (Stefko et al, 2020), and competitiveness (Kliuchnikava, 2022;Janovska et al, 2012) that positively affect their performance (Stefko et al, 2019), and competencies of companies to manage their innovation potential (Kolková et al, 2022), production capacity (Kutac et al, 2013), and financial issues (Charaia et al, 2021). Innovations also carry high importance for regions that significantly impact economic development in various areas (Jemala 2021).…”
Section: Literature Reviewmentioning
confidence: 99%